Temperature dependence of the angle-dependent magnetoresistance oscillations in alpha-(BEDT-TTF)(2)KHg(SCN)(4) - Honold, M; House, A; Blundell, S; Singleton, J; Perenboom, J; Hayes, W; Kurmoo, M; Day, P (1997)
Angle dependent magnetoresistance oscillations (AMRO) have been studied for the charge-transfer salt alpha-(BEDT-TTF)(2)KHg(SCN)(4). This material possesses a spin-density-wave (SDW) groundstate exhibiting AMRO with pronounced minima attributable to quasi-one-dimensional (Q1D) sections of Fermi surface (FS). Increasing the temperature or the magnetic field produces a change in the AMRO with the strong minima disappearing while pronounced peaks simultaneously evolve. These maxima are ascribable to a Q2D FS pocket. The change in form of the AMRO is thus associated with a reordering of the FS. This is brought about by removal of the SDW state causing reversion of the FS to the form close to that predicted by bandstructure calculations. The phase boundary between these two regimes has been tracked using AMRO from the high temperature limit to the high field limit for the first time and the shape of the Q2D sections of FS derived.